Sold on language how advertisers talk to you and what this says about you - Sedivy, Julie; Carlson, Greg N. 1948- (Wiley-Blackwell, 2011)
Sold on language examines how the competitive marketplace shapes the ways in which commercial and political advertisers speak to us.: Authored by a team of highly respected language scientists; Written in an informal style with many examples drawn from popular culture; Communicates ideas and research findings about language and the mind, revealing the mental processes behind the daily interactions we all have with contemporary advertising; Brings together insights from fields as varied as linguistics, philosophy, social psychology, behavioral economics, and political science.